Paciente masculino de 62 años con hipertensión y diabetes mellitus tipo 2. - Cevallos Sellan, Azalia Judith (2019)
The following clinical case is about a patient with hypertension 20 years ago. Within the family pathological history of a deceased mother with type 2 diabetes mellitus, she consults for presenting a clinical picture of nausea, imbalance, low back pain, headache, polyuria, polyphagia, polydipsia, blurred vision, weakness, with fear of developing diabetes, already that her breast suffered from this disease, a comprehensive nutritional assessment is performed and a grade I obesity with moderate cardiovascular risk is determined by the Body Mass Index; he was carried out nutritional biochemical tests in which his results reflect hyperglycemia, hypertriglyceridemia, hypercholesterolemia, elevated glycosylated hemoglobin and in the end he is diagnosed with Type 2 Diabetes mellitus; The physical examination does not reveal signs that make us suspect malnutrition, an eating plan is made depending on the caloric needs of the patient, the type of diet that should be taken will be hypo-sodium of 2-4gr / day, low in saturated fat, high in fiber that will be divided into 4 meals a day with a snack and its 3 main meals that corresponds (breakfast, lunch and snack) considering that dairy products will be skimmed, increasing the intake of complex carbohydrates, vegetables, fruits and vegetables, Including the physical activity that must be carried out, since this activity will improve your cardiovascular function because for each kg the patient drops, the blood pressure is estimated to decrease by 1.2 mm Hg, through monitoring and monitoring you can see an improvement in the patient, his biochemical tests varied but there is still hypertriglyceridemia and hyperglycemia, in a patient with these types of conditions s energy requirements are: proteins from 0.8 to 1 g / kg / day, carbohydrates from 3 to 5 g / kg / day and lipids 0.8-0.9 g / kg / day.